2011
DOI: 10.1007/s11468-010-9193-0
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Lens with Multiple-Turn Spiral Nano-Structures

Abstract: In this paper, we investigate the focusing properties of a plasmonic lens with multiple-turn spiral nano-structures, and analyze its field enhancement effect based on the phase matching theory and finite-difference time-domain simulation. The simulation result demonstrates that a left-hand spiral plasmonic lens can concentrate an incident right-hand circular polarization light into a focal spot with a high focal depth. The intensity of the focal spot could be controlled by altering the number of turns, the rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The "etched ring" structures are similar to the plasmonic lens designs that exist in the literature [14]. In a plasmonic lens structure, the period has to be chosen so as to match the SP wavelength to maximize the focusing and, therefore, the E-field intensity that dominates the resultant SERS signal intensity [20], [21]. Accordingly, the period of the "etched ring" structure is chosen to match the SP wavelength (calculated as 605 nm corresponding to the incident wavelength of 632.8 nm) in order to maximize the focusing.…”
Section: Sers Experiments and Resultsmentioning
confidence: 99%
“…The "etched ring" structures are similar to the plasmonic lens designs that exist in the literature [14]. In a plasmonic lens structure, the period has to be chosen so as to match the SP wavelength to maximize the focusing and, therefore, the E-field intensity that dominates the resultant SERS signal intensity [20], [21]. Accordingly, the period of the "etched ring" structure is chosen to match the SP wavelength (calculated as 605 nm corresponding to the incident wavelength of 632.8 nm) in order to maximize the focusing.…”
Section: Sers Experiments and Resultsmentioning
confidence: 99%
“…After the single turn spiral slit was investigated, the performance of multiple-turn ASS shown in Figure 5 was reported in 2011 [ 44 ]. Based on the same phase matching theory, such a multiple-turn spiral structure works in a more effective and practical way for the application of plasmonic lens because the increasing turns will improve the coupling effects of the generated SPP wave.…”
Section: Different Structural Constructionsmentioning
confidence: 99%
“…Spiral-shaped gratings have been extensively studied by several authors during recent years [2,[5][6][7][8][9]. In particular, Ohno and Miyanishi [6] reported the first study of surface plasmon chirality induced by Archimedes' spiral grooves.…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, Gorodetski et al [7] showed how a near-field vortex surface mode with a spin-dependent topological charge can be obtained and how it can produce the phenomenon of polarization-sensitive focusing. This particular phenomenon has been exploited by many other authors, such as Miao et al [8], who investigated the focusing properties of a plasmonic lens with multiple-turn spiral nanostructures, and analyzed its field enhancement effect. Another example of combining SPP modes generated by a PVL with nanofocusing capabilities of a plasmonic conical structure is given in [9], where high field enhancement on the nanoscale region is observed.…”
Section: Introductionmentioning
confidence: 99%